Knowledge of aged women about Sexually Transmitted Infections - Amanda Barth Gomes; Rosiane Filipin Rangel; Caroline de Leon Linck; Emanuelli Mancio Ferreira da Luz; Oclaris Lopes Munhoz; Silomar Ilha (Universidade Federal do Ceará, 2024)
Objective: to understand the knowledge of aged women about Sexually Transmitted Infections. Methods: a qualitative study with 11 aged women from a social group at a Basic Health Unit. Data was collected individually through semi-structured interviews, coded using NVIVO software, and analyzed using Thematic Content Analysis. Results: four categories emerged: Sexually Transmitted Infections known by the elderly; Different forms of transmission; Forms of prevention and detection; and Barriers to Knowledge and Sexually Transmitted Infections care. Conclusion: participants' knowledge of Sexually Transmitted Infections was observed, especially HIV, syphilis, and gonorrhea. There was a gap in knowledge about the distinction between HIV infection and AIDS. The lack of information about active sexuality is a barrier that interferes with safe sexual practice. Contributions to practice: understanding the knowledge of aged women about Sexually Transmitted Infections provides information that can help plan and implement measures to prevent these infections.